ESSAY WRITING TERMS - Akhrorova Ruzikhon Usmanovna; Murtazoxonov Jamsher Ganijon ugli (Zien Journals, 2022)
This article briefly explains the structure and order of writing an essay, and also talks about the different types of essays, depending on the purpose of writing it, what type it belongs to
Keywords: essay; plan; composition; opinion